2004
DOI: 10.1016/j.neuropsychologia.2004.05.005
|View full text |Cite
|
Sign up to set email alerts
|

The differential involvement of inferior parietal lobule in number comparison: a rTMS study

Abstract: Number processing is known to involve several sites within the posterior regions of parietal cortex. Here, we investigated whether neural activity in the inferior parietal lobule (IPL) is essential for number processing, by observing the effects of interfering with its activity during the execution of a standard number comparison task. Subjects performance on the task was significantly slowed down when we delivered trains of repetitive transcranial magnetic stimuli (rTMS) to the posterior parietal scalp site o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
50
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 52 publications
5
50
0
Order By: Relevance
“…These visuospatial brain regions seem to play a major role in numerical magnitude processing . As reviewed in the Introduction section, this was supported by several lines of research employing different methodologies such as split-brain patient research (Cohen & Dehaene, 1996), fMRI (Chochon et al, 1999), and rTMS (R. Cohen Kadosh, K. Cohen Kadosh, Schuhmann, et al, 2007), although not by others (e.g., Sandrini et al, 2004). Because subtraction involves magnitude manipulation along the mental number line (e.g., Pica et al, 2004), it is likely to be subserved by the right parietal cortex (especially as compared to multiplication, which relies more on verbal processing as discussed earlier).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These visuospatial brain regions seem to play a major role in numerical magnitude processing . As reviewed in the Introduction section, this was supported by several lines of research employing different methodologies such as split-brain patient research (Cohen & Dehaene, 1996), fMRI (Chochon et al, 1999), and rTMS (R. Cohen Kadosh, K. Cohen Kadosh, Schuhmann, et al, 2007), although not by others (e.g., Sandrini et al, 2004). Because subtraction involves magnitude manipulation along the mental number line (e.g., Pica et al, 2004), it is likely to be subserved by the right parietal cortex (especially as compared to multiplication, which relies more on verbal processing as discussed earlier).…”
Section: Discussionmentioning
confidence: 96%
“…Andres and colleagues (2005) found significant increases in RTs when subjects were comparing digits following an rTMS-induced disruption in the left posterior parietal cortex. Sandrini et al (2004) also found that subjects' performance on a number-comparison task was significantly slowed down when trains of repetitive TMS were delivered to their posterior parietal scalp site overlying the left inferior parietal lobule.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Several neuroimaging findings indicate that the intraparietal sulcus (IPS) and the angular gyrus (ANG) in the posterior parietal cortex (PPC) are critically involved in numerical cognition (Cohen Kadosh et al, 2005;Pesenti et al, 2000;Pinel et al, 1999Pinel et al, , 2001Zago et al, 2001; for reviews, see Brannon, 2006;Dehaene, 2003;Rickard et al, 2000). Support for the role of these regions in numerical processing has also come from studies using transcranial magnetic stimulation (TMS) (Cappelletti et al, 2007;Göbel et al, 2001;Rusconi et al, 2005;Sandrini et al, 2004).…”
Section: Introductionmentioning
confidence: 99%